THE ANALYSIS OF VERBAL INTERACTION BETWEEN TEACHER AND STUDENTS IN THE CLASSROOM AT SMAN 5 BARRU - Indah Faradia; Nurdevi Bte Abdul; Ratu Yulianti Natsir (English Language Teaching Methodology, 2021)
The objective of the research can be used to get the literature and existing research on verbal interaction between teacher and students and gives beneficial reference for future research on the way teacher influences student talk in classroom and The result of this research can be used as information to teacher understand the good interation in class. As for the obstacles faced by teacher that was at different levels of students’ ability so that must think of different techniques in improving the ability of each student and was constrained at a short time during. This research methodology apply qualitative approach and descriptive method. The goals of this study are to get description of how the verbal interaction between teacher and students conducted and the way teacher influences student talk in classroom interaction. This research was done at class XII IPA there were 30 students and used only 5 students and 1 teacher use in a sample. The result of the this research the verbal interaction between teacher and students in the classroom for XI grade students at SMAN 5 Barru. Verbal interactions between teachers and students have a relationship with each other and influence each. As for teacher strategies to get student’s response, There are 4 strategies to get students response which include the use of students and the use of various sources or activities in learning, this means that in the formulation of new strategies until the work plan preparation process has not yet achieved action.